The role of platelet activation in determining response to therapy in patients with primary nephrotic syndrome. (September 2013) - Kocyigit, Ismail; Yilmaz, Mahmut Ilker; Şimşek, Yasin; Unal, Aydin; Sipahioglu, Murat Hayri; Eroglu, Eray; Dede, Fatih; Tokgoz, Bulent; Oymak, Oktay; Utas, Cengiz
<x xml:space="preserve">Abstract</x> To test the role of platelet activation in the prognosis of nephrotic syndrome (NS), we evaluated the mean platelet volume (MPV) in patients with NS undergoing treatment. In this prospective, multicenter clinical study 156 patients with primary NS under treatment were assigned and followed for one year. Patients were divided into three groups for complete remission, partial remission, and resistance. Biochemical parameters, estimated glomerular filtration rate, proteinuria level, and MPV levels were compared at baseline and 12 months after treatment. MPV, proteinuria, total cholesterol, triglyceride, LDL cholesterol, HDL cholesterol, total protein, albumin, and hs-CRP levels significantly decreased in partial and complete remission group after 12 months compared to the baseline (p < 0.05). However, MPV levels significantly increased and only LDL cholesterol significantly decreased in the resistance group (p < 0.05). Univariate analyses demonstrated that ΔMPV was significantly associated with Δproteinuria (r = 0.41, p < 0.001), Δhs-CRP (r = 0.39, p < 0.001), and ΔAlbumin (r = −0.30, p < 0.001). We found that ΔAlbumin (β = −0.33, p < 0.001), ΔTotal cholesterol (β = −0.20, p = 0.011), and Δhs-CRP (β = 0.19, p = 0.018) were statistically significant predictors of the Δproteinuria in multiple regression analysis. In subjects with primary NS, MPV is associated with the prognosis or the disease. This study provides the background for longer trials and the role of platelet activation in NS.